2017
DOI: 10.1002/adhm.201700131
|View full text |Cite
|
Sign up to set email alerts
|

Injectable Mussel‐Inspired Immobilization of Platelet‐Rich Plasma on Microspheres Bridging Adipose Micro‐Tissues to Improve Autologous Fat Transplantation by Controlling Release of PDGF and VEGF, Angiogenesis, Stem Cell Migration

Abstract: Platelets-rich plasma (PRP) can produce growth factors (GFs) to improve angiogenesis. However, direct injection of PRP does not lead to highly localized GFs. The current study employs a mussel-inspired polydopamine to immobilize PRP on gelatin microspheres (GMs) with the purpose of bridging adipose micro-tissues to help implanted fat survive (GM-pDA-PRP). Enhanced PRP adhesion leads to a prolonged and localized production of GFs, which is verified by platelet counting and by ELISA of vascular endothelial growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 73 publications
1
28
0
Order By: Relevance
“…Hence, PRP has been used for fat and skin repair and as an adhesive for wound closure. It has, for example, been shown that PRP (mean enrichment 6.4-fold) immobilized on gelatin microspheres improved the engraftment and particularly the vascularization of transplanted fat upon subcutaneous implantation [53]. Promising results were also reported for the application of a mixture of PRP with heparin-conjugated fibrin for the treatment of full-thickness wounds in mice.…”
Section: Prp In Tissue-engineered Constructsmentioning
confidence: 71%
“…Hence, PRP has been used for fat and skin repair and as an adhesive for wound closure. It has, for example, been shown that PRP (mean enrichment 6.4-fold) immobilized on gelatin microspheres improved the engraftment and particularly the vascularization of transplanted fat upon subcutaneous implantation [53]. Promising results were also reported for the application of a mixture of PRP with heparin-conjugated fibrin for the treatment of full-thickness wounds in mice.…”
Section: Prp In Tissue-engineered Constructsmentioning
confidence: 71%
“…Lots of basic science studies on cell cultures and animal models as well as human clinical trials supported the application of PRP. [26][27][28] Numbers studies have focused on its effect on multiple stem cells proliferation, [29][30][31][32] EnMSCs could be conveniently segregated from menstrual blood and expanded to create almost unlimited supplies. There are several advantages of EnMSCs, including embryoniclike properties, noninvasive isolation procedures, and improved function.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have veried that various biomolecules can easily conjugate onto the surface of the PDA-coated materials, depending on the reaction of catechols with thiols and amines, such as BMP-2, VEGF and bFGF. 26,27,34 Zhou et al successfully immobilized P24 peptide on polydopamine coated nHA/RHLC/PLA scaffolds and found that PDA-assisted coating could effectively immobilize P24 peptide on the surface of nHA/RHLC/PLA scaffold and allowed for its controlled release. 35 Another study found that immobilized bFGF on PDA coated PLGA electrospun brous scaffolds showed higher bFGF immobilization efficiency than PLGA electrospun brous scaffolds.…”
Section: Adsorption and Release Of Igf-1 And Bmp-2mentioning
confidence: 99%